The Meaning of ‘Amânah’ and 'Trust' in the Appointment of Nâzhir in Indonesian Endowment Regulations - Yumarni, Ani; Suhartini, Endeh; Haqqi, Abdurrahman Raden Aji; Mulyadi, Mulyadi; Maryam, Siti (Universitas Islam Negeri Raden Intan Lampung, 2023)
This article analyzes the realization of the professionalism principle for the nâzhir (waqf organiser) as conceptualized in waqf (endowment) law. One of the nâzhir requirements in the endowment law is the amânah which is interpreted as human responsibility covering the horizontal/insâniyyah and the hereafter (transcendental/ilâhiyyah) dimensions. By using a statutory approach (statute approach) and a conceptual approach, this research finds the fact that endowment (endowments) is the tabarru' (voluntary) contract; the amânah principle as contained in the endowment pledge has a similar meaning to the concept of trust in a general sense. The concept of trust in a general sense and the concept of amânah/trust in Islamic law are both forms of trust from one party to another with the conditions set out in Article 10 of the Endowment Law and the endowment pledge deed